EFFECT OF EXOGENOUSE LOCAL LIGNINOLYTIC CRUDE ENZYMES ON IN VITRO DIGESTABILITY AND LIGNIN CONTENT OF ROUGHAGES - & Al-Khateeb, Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
In current study use local ligninolytic crude extract enzyme (HAMU 8%) to improve IVDMD and reducing lignin content. The result suggest that treated wheat straw (WS), Corncobs (Cc), alfalfa hay (AH), by HAMU increased significantly (p <0.05) in vitro dry matter digestibility (IVDMD) and reduction in lignin content, However, extra enzyme improvement is shown with Corncobs treated with HAMU (average improvement, 19.84%) and lower improvement was shown in alfalfa hay treated with HAMU (average improvement, 10.07%). The higher reduction (P<0.01) in lignin content was shown in Cc treated with HAMU from 9.8 to 7.901%, with average reduction 1.899%; when the lower reduction was observed significantly (P<0.05) with AH treated from 8.26 to 7.77%, average reduction was 0.49%.It could be recommended, treated low quality roughages with HAMU improved the nutritional value of roughages through the digestion of Structural carbohydrates.